2013
DOI: 10.5999/aps.2013.40.3.247
|View full text |Cite
|
Sign up to set email alerts
|

A Salvage Operation for Total Penis Amputation Due to Circumcision

Abstract: Circumcision is one of the most common rituals in Jewish and Islamic cultures. It may also be performed for phimosis correction or the treatment of recurrent balanitis. Although circumcision is considered to be a technically easy and safe surgical procedure with no significant risk, it may lead to severe complications such as necrotizing fasciitis or total penis amputation. In this report, we present a case of penis amputation at two levels occurring with third-degree burns due to electrocautery during circumc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…[11,12] As a treatment alternative in cases where microsurgical repair is not feasible following dysepithelization, penis is embedded in the inguinal region so as to maintain vitality of the penis. [12] Another important complication of circumcision is urethrocutaneous fistula (UCF). Despite such a high incidence of circumcision, only a few cases of UCF have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] As a treatment alternative in cases where microsurgical repair is not feasible following dysepithelization, penis is embedded in the inguinal region so as to maintain vitality of the penis. [12] Another important complication of circumcision is urethrocutaneous fistula (UCF). Despite such a high incidence of circumcision, only a few cases of UCF have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the cases reported in Japan, amputation was carried out at the proximal part in majority of the cases; the peripubic area in 7.4%, the proximal part in 88.9%, and the glans in 3.7% . Complete penile glans amputation has been reported in infants as a complication of circumcision . However, in adults, only one case of self‐amputation at the glans has been reported in Japan; the report only included an abstract and did not provide the detailed procedure.…”
Section: Discussionmentioning
confidence: 99%
“…At this level, two arteries and a venous anastomosis can be carried out, which leads to an adequate vascular supply to the distal replant. Ince and Gundeslioglu [9] reported that for distal penis amputations in which the repair cannot be achieved by replantation, burying the penis underneath the inguinal area may be an alternative salvage operation to replantation.…”
Section: Discussionmentioning
confidence: 99%